Representasi Iklan Kecantikan Di Media Massa Dalam Perspektif Islam - Intihaul Khiyaroh (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Women represented in advertisements in the mass media have beauty, perfection in both their body, face and behavior. Beauty advertisements in the mass media use women as the main subject in their sales promotions. Advertisements for skincare, bodylation, lipstick, bath soap, shampoo, and tools that are not necessarily needed by women are often found in the mass media, taking turns filling people's daily lives. Ironically, many of the women themselves are not aware of the ad's bias, even considering it as a natural thing and does not need to be questioned through the advertisement. The mass media are free to reinforce the existing views, beliefs, attitudes and norms of women. These beliefs include the importance of women being physically beautiful, fit, beautiful, slim, young and so on. In the Islamic perspective, women have a genitalia limit that is not allowed to be displayed in front of the opposite sex, let alone shown in advertisements with the audience consisting of various age groups.